Non‐Precious Metal Catalysts Prepared By Zeolitic Imidazolate Frameworks: The Ligand Influence to Morphology and Performance1. Issue 4 (6th July 2016) - Barkholtz, H. M.; Chong, L.; Kaiser, Z. B.; Liu, D. J.
Abstract: A new, "one‐pot" synthesis to produce highly active non‐PGM electrocatalysts for PEM fuel cells was previously developed by pyrolyzing Fe doped zeolitic imidazolate framework (ZIF) materials prepared by solid‐state interaction. Excellent catalytic oxygen reduction reaction (ORR) activities were found through rotating ring‐disk electrode (RRDE) and single fuel cell tests. In this study, we compared the ORR activities and structural properties of two catalysts derived from ZIFs containing imidazole and methyl imidazole ligands, respectively. Our results indicate that alkyl group substitution in the imidazolate ligand has a profound effect on the final catalyst performance.